A NOTE ON THE RIGHT TRUNCATED WEIBULL DISTRIBUTION AND THE MINIMUM OF POWER FUNCTION DISTRIBUTIONS - Jodra, Pedro (Revstat, 2022)
* In this note, the right truncated Weibull distribution is derived as the distribution of the minimum of a random number of independent and identically distributed random variables. Specifically, the independent random variables have a common power function distribution and the random number has a zero-truncated Poisson distribution. Keywords: * right truncated Weibull distribution; power function distribution; truncated Poisson distribution; minimum of random variables. AMS Subject Classification: * 60E05, 62E15, 62N05.